THE CURRENT CHALLENGES IN THE FIELD OF ARTIFICIAL INTELLIGENCE (Web of Technology: Multidimensional Research Journal, 2025)
This paper explores the current challenges in the field of artificial intelligence (AI), focusing on its development, implementation, and ethical considerations. It examines the technical, social, and regulatory obstacles that hinder the broader adoption of AI technologies. The study also highlights the implications of these challenges for Uzbekistan, emphasizing the need for strategic planning and educational initiatives to address AI-related issues. Recommendations are provided to align AI advancements with global trends while ensuring ethical and sustainable development in the region.